Kontekstualisasi Pemikiran Syekh Nawawi Al-Bantani tentang Pendidikan Akhlak di Madrasah Tsanawiyah - Muhtar Luthfie Al Anshory (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2020)
Various problems of students that arise in the world of education make the institution are accused as the root of the problems in printing their students. The emergence of this problem is due to the lack of application of moral education especially in Islamic school, in this case every Islamic school needs to contextualize the thought of Shekh Arsyad Al Banjari as a reference in educating, as we know that he is one of Indonesia's 'Ulama' who has the title of Al-Sayyid Al-'Ulama Al -Hijaz who had been once an "Imam" (A leader of Communal player) at the Grand Mosque in Mecca, many of his works which when contextualized into education are still very relevant. From his various ideas about moral education, it is feasible to be used as a foundation for the implementation of moral education in every school. The purpose of moral education is none other than to form students so that they have good character, ethics, and morals apart from qualified knowledge. The application of moral education certainly does not escape the collaboration of various parties, both parents and teachers as role models in schools, the goal is to be able to supervise students to be more intense.